ENGINEERED OVEN AS AN ALTERNATIVE METHOD ON STAMP CANTING SOLDERING PROCESS - I Made Arya Utamaningrat; Robets Christiawan; Suparjo Suparjo; Hadi Sumarto; Farida Farida (Balai Besar Kerajinan dan Batik, 2021)
Batik is a process of attaching wax onto a fabric to block color from entering it. This process is done using a tool called canting. There are two kind of canting, writing canting and stamp canting, that is respectively use to make written batik and stamp batik. Stamp canting was made to accelerate the process of making batik fabric, while maintaining the standard of batik itself. It was made using copper that is stack in certain way and burned on a pile of charcoal to make sure the adhesive material (patri) melt. This research aims to accelerate the process of soldering stamp canting using engineered oven instead of using charcoal. the oven engineered in this research uses Liquid Petroleum Gas (LPG) as its main source of heat. It was made not only to accelerates the process, but also to make sure the consistency of the heat along the process of burning which will directly affecting the end product of stamp canting. The method used in this research includes: literature studies, field studies, oven engineering, making canting samples, test, and reporting. The result of this research shows that the oven is able to work and melt the standardized patri on stamp canting.